2021
DOI: 10.1186/s13034-021-00423-0
|View full text |Cite
|
Sign up to set email alerts
|

Harsh parenting and non-suicidal self-injury in adolescence: the mediating effect of depressive symptoms and the moderating effect of the COMT Val158Met polymorphism

Abstract: Background Previous studies have suggested that negative parenting environments, especially harsh parenting, are a specific risk factor for non-suicidal self-injury (NSSI). However, the potential mechanism between harsh parenting and NSSI has not been explored. Based on the experiential avoidance model and empirical research, we aimed to examine whether depressive symptoms are a mediator between harsh parenting and NSSI. Moreover, the catechol-O-methyltransferase (COMT) Val158Met polymorphism r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…Particularly, among adolescents with Val/Val genotype but not Met allele, parent-adolescent conflict allows a significantly positive prediction of depressive symptoms. This result is consistent with previous research that adolescents with Val/Val homozygotes may be more susceptible to negative family environments, which, in turn, may trigger depressive symptoms [ 15 , 29 ]. In a high level of parent-adolescent conflict, negative interactions with parents can affect subcortical limbic regions associated with emotional reactivity [ 48 ] and thus develop depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Particularly, among adolescents with Val/Val genotype but not Met allele, parent-adolescent conflict allows a significantly positive prediction of depressive symptoms. This result is consistent with previous research that adolescents with Val/Val homozygotes may be more susceptible to negative family environments, which, in turn, may trigger depressive symptoms [ 15 , 29 ]. In a high level of parent-adolescent conflict, negative interactions with parents can affect subcortical limbic regions associated with emotional reactivity [ 48 ] and thus develop depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Valencia-Agudo et al retrieved 39 studies on NSSI indicated that depressive symptoms is observed to prospectively predict future NSSI [ 13 ]. Furthermore, preliminary research suggested that depressive symptoms played an important mediating role between family risk factors (e.g., parental rejection, harsh parenting) and adolescent NSSI [ 14 , 15 , 16 ]. A longitudinal research by Zhu et al, with a sample of 1987 Chinese adolescents, found that parental rejection predicted adolescents NSSI six months later through depressive symptoms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, by confirming the detrimental effects of harsh parenting on adolescents’ depressive symptoms and suicidal ideation, we provide evidence that educators should not only pay attention to adolescents’ mental health but also focus more on parenting styles and help parents recognize the influence of their style of parenting on the parent–child relationship [ 20 , 85 ]. Several strategies could be used to prevent harsh parenting by Chinese parents.…”
Section: Discussionmentioning
confidence: 75%